Sox2 is required for maintenance and regeneration, but not initial development, of hair cells in the zebrafish inner ear - Millimaki, Bonny B. (2009)
Sox2 has been variously implicated in maintenance of pluripotent stem cells or, alternatively, early stages of cell differentiation, depending on context. In the developing inner ear, Sox2 initially marks all cells in the nascent sensory epithelium and, in mouse, is required for sensory epithelium formation. Sox2 is eventually downregulated in hair cells but is maintained in support cells, the functional significance of which is unknown. Here we describe regulation and function of sox2 in the zebrafish inner ear. Expression of sox2 begins after the onset of sensory epithelium development and is regulated by Atoh1a/b, Fgf and Notch. Knockdown of sox2 does not prevent hair cell production, but the rate of accumulation is reduced due to sporadic death of differentiated hair cells. We next tested the capacity for hair cell regeneration following laser-ablation of mature brn3c:gfp-labeled hair cells. In control embryos, regeneration of lost hair cells begins by 12 hours post-ablation and involves transdifferentiation of support cells rather than asymmetric cell division. In contrast, regeneration does not occur in sox2-depleted embryos. These data show that zebrafish sox2 is required for hair cell survival, as well as for transdifferentiation of support cells into hair cells during regeneration.